National Crime Surveys: Redesign Data, 1975-1979 ([Verlag nicht ermittelbar], 1987)
These data are a product of the National Crime Surveys Redesign Project. The purpose of the data collection was to create several different data files from existing public-use National Crime Surveys files. For each crime, information is gathered on the victim's housing unit and household and the incident itself. A personal history and interview are also included. Several data files contain National Crime Survey and Uniform Crime Report data on the following index crimes: robbery, larceny-theft, burglary, motor vehicle theft, rape, and aggravated assault.